Insights into the plant responses to drought and decoding the potential of root associated microbiome for inducing drought tolerance. Issue 2 (7th February 2021) - Mathur, Piyush; Roy, Swarnendu
Abstract: Global increase in water scarcity is a serious problem for sustaining crop productivity. The lack of water causes the degeneration of the photosynthetic apparatus, an imbalance in key metabolic pathways, an increase in free radical generation as well as weakens the root architecture of plants. Drought is one of the major stresses that directly interferes with the osmotic status of plant cells. Abscisic acid (ABA) is known to be a key player in the modulation of drought responses in plants and involvement of both ABA‐dependent and ABA‐independent pathways have been observed during drought. Concomitantly, other phytohormones such as auxins, ethylene, gibberellins, cytokinins, jasmonic acid also confer drought tolerance and a crosstalk between different phytohormones and transcription factors at the molecular level exists. A number of drought‐responsive genes and transcription factors have been utilized for producing transgenic plants for improved drought tolerance. Despite relentless efforts, biotechnological advances have failed to design completely stress tolerant plants until now. The root microbiome is the hidden treasure that possesses immense potential to revolutionize the strategies for inducing drought resistance in plants. Root microbiota consist of plant growth‐promoting rhizobacteria, endophytes and mycorrhizas that form a consortium with the roots. Rhizospheric microbes are proliferous producers of phytohormones, mainly auxins, cytokinin, and ethylene as well as enzymes like the 1‐aminocyclopropane‐1‐carboxylate deaminase (ACC deaminase) and metabolites like exopolysaccharides that help to induce systemic tolerance against drought. This review, therefore focuses on the major mechanisms of plant‐microbe interactions under drought‐stressed conditions and emphasizes the importance of drought‐tolerant microbes for sustaining and improving the productivity of crop plants under stress.